The Risk of Depression and Suicide among the University Students of Kuwait; A Cross-Study of Three Universities - Dinkha, Juliet (2012)
Depression and Suicide risk was studied in students of three leading universities of Kuwait, The American University of Kuwait (AUK), Gulf University for Science and Technology (GUST), and Australian College of Kuwait (ACK). Participants told in advance they would be required to fill out a BDI-II and a questionnaire formulated to gain data on students understanding of depression and suicide. Data from the questionnaire was subjective; therefore, only common words or themes expressed were considered and recorded. The remaining responses were place in a category of other. The result was that although depression was more significant in the participants of the study, the knowledge of depression and even the acceptance of depression existing in Kuwait was limited.